ANALISIS LINTAS PERTUMBUHAN DAN PRODUKSI TERHADAP PROTEIN KACANG TUNGGAK (Vigna unguiculata L) GENERASI M2 - Yukarie Ayu Wulandari; Sobir Sobir; Syarifah Iis Aisyah (Fakultas Pertanian - UMJ, 2021)
Cowpea (V. unguiculata L) can be developed as a source of vegetable protein because it contains relatively high protein and high lysine. The protein content in seeds is an accumulation of character components that play a role in protein formation, whose relationship can be predicted using cross correlation and analysis coefficients. The study was carried out in the experimental garden of Pasir Kuda PKHT of IPB in February - May 2018. Protein analysis is carriedout in the Testing Laboratory of the Department of Agronomy and Horticulture, Faculty of Agriculture, IPB in June - July 2018. The study was conducted using 30 putative mutant test genotypes of M2 generation result from the mutation of gamma ray irradiation and KM4 genotype as a comparison which was repeated three times. The protein content of the seeds was analyzed using the Kjeldahl method and then analyzed the variance, correlation coefficient and path. The results showed that M2 generation putative mutants showed diversity for the character of protein content in cowpea seeds. The protein content in cowpea seeds can be predicted through the character of plant height and number of branches.